New antibacterial cadiolide analogues active against antibiotic-resistant strains. Issue 21 (1st November 2020) - Bekri, Sarra; Desriac, Florie; Barreau, Magalie; Clamens, Thomas; Gallavardin, Thibault; Nahenec-Martel, Patricia Le; Vieillard, Julien; Datoussaid, Yazid; Choukchou-Braham, Noureddine; Lesouhaitier, Olivier; Franck, Xavier; Leleu, Stéphane
Graphical abstract: Abstract: The synthesis of new cadiolide analogues was carried out using a one-pot multi component synthesis. The antibacterial activity of these molecules was evaluated on standard and antibiotic resistant bacterial strains chosen for their involvement in human health or in food-born poisoning. Four molecules have shown good activities with MICs of 2 μg/mL −1 . The introduction of an indole group or the conversion of the lactone into lactam have highlighted two new families of molecules with promising antibacterial activity. In addition, most of these active molecules are devoid of cytotoxic activity against keratinocyte cells.